Answer:
Follows are the solution:
Step-by-step explanation:
A + B = C
Its response decreases over time as well as consumption of a reactants.
r = -kAB
during response A convert into 2x while B convert into x to form 3x of C
let's y = C
y = 3x
Still not converted sum of reaction
for A: 100 - 2x
for B: 50 - x
Shift of x over time
![(dx)/(dt) = (-k(100 - 2x))/((50 - x))](https://img.qammunity.org/2021/formulas/chemistry/high-school/ihoq5o4occt3v34i8u8hcekac2lwu37ikn.png)
Integration of x as regards t
![(1)/([(100 - 2x)(50 - x)]) dx = -k dt\\\\(1)/(2[(50 - x)(50 - x)]) dx = -k dt\\\\\ integral\ (1)/(2[(50 - x)^2]) dx =\ integral [-k ] \ dt\\\\(-1)/([100-2x]) = -kt + D \\\\](https://img.qammunity.org/2021/formulas/chemistry/high-school/ftr2uclda66bmfwb8jah72419lfvwdzazw.png)
D is the constant of integration
initial conditions: t = 0, x = 0
![(-1)/([100-2x]) = -kt + D \\\\( -1)/([100]) = 0 + D\\\\D= (-1)/(100)\\\\](https://img.qammunity.org/2021/formulas/chemistry/high-school/mqca55b2d1kds2x5r4m0rl4d5b30lem0da.png)
hence we get:
![(-1)/([100-2x])= -kt -(1)/(100)\\\\or \\\\ (1)/((100-2x)) = kt + (1)/(100)](https://img.qammunity.org/2021/formulas/chemistry/high-school/ma09kxr2q8oo0pbtdbgw9cp4relwe2xy7r.png)
after t = 7 minutes ,
![C = 10 \ g = 3x](https://img.qammunity.org/2021/formulas/chemistry/high-school/atz97hzupxxjn2h45kzwl81zko450mzmaf.png)
![3x = 10\\\\x = (10)/(3)](https://img.qammunity.org/2021/formulas/chemistry/high-school/pv4n4dfdbqkqg3jkvruqydkla0kxmec59x.png)
Insert the above value x into
equation
to get k.
![\to (1)/((100-2* (10)/(3))) = k * (7) + (1)/(100) \\\\ \to (1)/((100- 2 * 3.33)) = (700k + 1)/(100) \\\\ \to (1)/((100-6.66)) = (700k + 1)/(100)\\\\ \to (1)/(93.34) = (700k + 1)/(100) \\\\](https://img.qammunity.org/2021/formulas/chemistry/high-school/3eznemfx726lrfzo8q86qnfbbi45ofikvv.png)
![\to 100 = 93.34(700k + 1) \\\\ \to 100 = 65,338k + 700 \\\\ \to 65,338k = -600 \\\\ \to k = (-600)/( 65,338) \\\\ \to k= - 0.0091](https://img.qammunity.org/2021/formulas/chemistry/high-school/5nuoc0v1ooq8u1vljp5xxplnnzpo2oyxrw.png)
therefore plugging in the equation the above value of k
![\to (1)/((100-2x)) = kt +(1)/(100) \\\\\to (1)/((100-2x)) = -0.0091t + (1)/(100)\\\\\to (1)/((100-2x)) = (1 -0.91t)/(100)\\\\\to (1)/(2(50-x)) = (1 -0.91t)/(100)\\\\\to (1)/((50-x)) = (1 -0.91t)/(50)\\\\\to 50= (1-0.91t)(50-x)\\\\\to 50 = 50-45.5t-x-0.91tx\\\\\to x+0.91xt= -45.5t\\\\\to x(1+0.91t)= -45.5t\\\\\to x=(-45.5t)/(1+0.91t)](https://img.qammunity.org/2021/formulas/chemistry/high-school/6whyvb9ox73xd4qjcjncdq9ylmri8vve3j.png)
Let y = C
, calculate C:
y = 3x
![y =3 * (-45.5t)/(1+0.91t)](https://img.qammunity.org/2021/formulas/chemistry/high-school/fycrxb0pt9zqzddd794hx7a2nnx104alcs.png)
amount of C formed in 28 mins
plug t = 28
![\to x = (-1274)/(1+25.48) \\\\\to x = (-1274)/(26.48) \\\\\to x= -48.26](https://img.qammunity.org/2021/formulas/chemistry/high-school/tx3xsi1l52ikso686d63nivszns762t7ox.png)
therefore amount of C formed in 28 minutes is = 3x = 144.78 grams
C:
![y =3 * (-45.5t)/(1+0.91t)](https://img.qammunity.org/2021/formulas/chemistry/high-school/fycrxb0pt9zqzddd794hx7a2nnx104alcs.png)
y= 136.5 =137